Life Since Then: Reconstructing Korean Women’s Educational Experiences and their Lives - Kyungmi Hyun (Adult Education Research Conference, 2002)
This study examines Korean women’s educational experiences during the Japanese colonial period in Korea (1910-1945). The primary research approach is discourse analysis of the language used in interview data and written documents.